The Responsibility of Local Governments and the Interfaith Harmony Forum in Regulating the Establishment of Houses of Worship in Indonesia - Joshua Sabam Jonathan Hutagalung; Matthew Benedictus Manuputty; Shabiha Elena Putri; Welly Gosal (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to analyze the role of local government in regulating the establishment of houses of worship in Indonesia through a case study of the Prayer House of the Indonesian Faithful Christian Church Congregation (GKSI) Padang in the City of Padang, West Sumatra. The regulation of the establishment of houses of worship under the Joint Regulation of the Minister of Religious Affairs and the Minister of Home Affairs No. 9 and No. 8 of 2006 grants significant authority to local governments in terms of administrative verification, facilitation of interreligious harmony, and conflict mediation. However, in practice, this authority often operates within a tension between maintaining public order and ensuring the protection of the constitutional right to freedom of religion. This research employs a qualitative method with a juridical-empirical approach and a case study design, utilizing the analysis of statutory regulations, official documents, media reports, and academic literature. The findings indicate that, in the case of GKSI Padang, the local government has functioned as both an administrative regulator and a conflict mediator. Nevertheless, its role as a guarantor of constitutional rights remains suboptimal, particularly in preventing vigilantism and ensuring the security of religious worship. This study recommends strengthening local government standard operating procedures based on principles of non-discrimination, accountability, and human rights protection in order to prevent similar conflicts in the future.